Public sector employees: Risk averse and altruistic? - Margaretha Buurman; Josse Delfgaauw; Robert Dur; Seth van den Bossche (Center for Economic Studies and ifo Institute (CESifo), 2012)
We assess whether public sector employees have a stronger inclination to serve others and are more risk averse than employees in the private sector. A unique feature of our study is that we use revealed rather than stated preferences data. Respondents of a large-scale survey were offered a substantial reward and could choose between a widely redeemable gift certificate, a lottery ticket, or making a donation to a charity. Our analysis shows that public sector employees are significantly less likely to choose the risky option (lottery) and, at the start of their career, significantly more likely to choose the pro-social option (charity). However, when tenure increases, this difference in pro-social inclinations disappears and, later on, even reverses. Further, our results suggest that quite a few public sector employees do not contribute to charity because they feel that they already contribute enough to society at work for too little pay.
Keywords: H10; J45; M52; 330; public service motivation; risk aversion; revealed preferences data; Öffentlicher Dienst; Risikoaversion; Altruismus; Niederlande